Abnormal expression and clinical significance of 25-hydroxyvitamin D and sFlt-1 in patients with preeclampsia. Issue 10 (October 2019) - Chen, Xinhua; Xi, Xuxia; Cui, Fan; Wen, Ming; Hong, Aijuan; Hu, Zemei; Ni, Juan
Objective: To determine the association between levels of serum 25-hydroxyvitamin D (25[OH]D) and soluble fms-like tyrosine kinase 1 (sFlt-1) in patients with preeclampsia. Methods: Clinical and demographic data were collected from patients with preeclampsia and healthy pregnant controls. Serum 25(OH)D and sFlt-1 levels were evaluated by enzyme-linked immunosorbent assay and their correlations were determined using Spearman's rank correlation coefficient. Associations between serum 25(OH)D and sFlt-1 levels and disease severity and clinical parameters were evaluated. Results: Significantly lower serum 25(OH)D and higher sFlt-1 levels were observed in patients with preeclampsia ( n = 100) versus controls ( n = 100), and 25(OH)D was inversely correlated with sFlt-1 in patients with preeclampsia. Serum 25(OH)D levels were reduced, while sFlt-1 concentration was increased in patients with severe versus mild preeclampsia. Serum 25(OH)D levels were reduced in late-onset versus early-onset severe preeclampsia. Patients with preeclampsia who had lower serum 25(OH)D or elevated sFlt-1 levels showed significantly higher blood pressure indexes versus those with higher 25(OH)D or lower sFlt-1. Conclusions: Low serum 25(OH)D and high sFlt-1 may be candidate biomarkers for preeclampsia diagnosis and prognosis.